ANALISIS KESALAHAN SISWA SMK DALAM MENYELESAIKAN SOAL MATERI LOGARITMA BERDASARKAN PROSEDUR KASTOLAN - Nadiyah Fitriyah; Citra Megiana Pertiwi; Anik Yuliani (IKIP Siliwangi, 2022)
Mathematics is very important to be taught to students so that they can have and apply mathematical thinking patterns in everyday life and become a reference for studying various other branches of science. One of the Mathematics materials is logarithm material where students often make mistakes when solving these problems, so this study aims to analyze student errors in solving a number of logarithm material problems using the Kastolan procedure. This study used a qualitative descriptive method with the research subject of 10 students of class X Pharmacy in one of the Vocational High Schools in West Bandung. The research instrument used a logarithm material description test instrument as many as 5 questions. Data analysis techniques applied are data reduction, data presentation, and drawing conclusions. Based on the results of the research data, it was concluded that students made conceptual errors, namely the inability of students to apply the concept of the properties used, procedural errors in which students could not solve the problem until they got the final solution, and technical errors occurred because students were wrong in doing calculations so as to produce answers wrong.